EVALUATION OF ANTAGONISTIC POTENTIAL OF TRICHODERMA HARZIANUM AND PSEUDOMONAS FLUORESCENS ISOLATES AGAINST GLOEOCERCOSPORA SORGHI CAUSING ZONATE LEAF SPOT OF SORGHUM - PUROHIT, JYOTIKA; SINGH, YOGENDRA; BISHT , SUNAINA; A. SRINIVASARAGHVAN (The Bioscan, 2013)
In an attempt to develop effective biocontrol system for management of zonate leaf spot caused by Gloeocercospora sorghi, fifteen isolates of Trichoderma harzianum and six isolates of Pseudomonas fluorescens were tested for their antagonistic potential against G.sorghi. Th-43 and Psf-28 isolates achieved maximum inhibition of radial growth of the test pathogen by (77.77%) and (56.66%) respectively under in vitro study. Effective isolates of T. harzianum (Th-43, 39, 32 and 31) and P. fluorescens (Psf-28, 11 and r) were selected on the basis of in vitro superiority and further evaluated in glasshouse and field conditions. Treatments were given as three foliar sprays at 35, 45 and 55 days after sowing under in vivo conditions (glasshouse and field conditions). In glasshouse conditions, maximum reduction in disease severity was obtained with Th-43 (57%) followed by Th-39 (53.63%) with three foliar sprays. Similarly, Th-39 (36.62%) showed maximum reduction in disease severity with three foliar sprays under field conditions. Thus, the present study demonstrates the possible role of T. harzianum and P. fluorescens in the induction of antagonistic compounds against G. sorghi.